Corporate Governance and Innovation in Malaysia (International Journal of Innovation and Business Strategy (IJIBS), 2024)
Corporate governance are the internal systems or means that direct and control corporations. It specifies the rules and practices to ensure accountability, fairness, and transparency in a company’s relationship with its stakeholders. Innovation considered as the development of a new idea, device or method is deemed to be affected by corporate governance mechanisms both positively and negatively around the world. For Malaysia, there wasn’t any study undertaken to show how different mechanisms of corporate governance namely; ownership concentration and characteristics of the board of directors affect innovation. This study is carried out with the purpose to find out how corporate governance affects innovation for Malaysian listed companies. It is a quantitative study using a combination of convenience and systematic random sampling methods to collect data from a population of 993 companies listed in Bursa Malaysia. Probit regression analysis is used to analyze the data. It is found out that meetings frequency of the board of directors has a significant positive relationship with innovation for Malaysian listed companies implying that frequent board meeting results in patent registrations. For other corporate governance mechanisms, there weren’t sufficient evidences available to conclude a significant positive or negative relationship with innovation.
Keywords: Innovation, corporate governance, ownership concentration, board of directors